Dynamics of Defective Hepatitis C Virus Clones in Reinfected Liver Grafts in Liver Transplant Recipients: Ultradeep Sequencing Analysis - Ohtsuru, Shigeru (American Society for Microbiology, 2013)
Hepatitis C virus (HCV) reinfects liver allografts in transplant recipients by replicating immediately after transplantation, causing a rapid increase in blood serum HCV RNA levels. We evaluated dynamic changes in the viral genetic complexity after HCV reinfection of the graft liver; we also identified the characteristics of replicating HCV clones using a massively parallel ultradeep sequencing technique to determine the full-genome HCV sequences in the liver and serum specimens of five transplant recipients with genotype 1b HCV infection before and after liver transplantation. The recipients showed extremely high genetic heterogeneity before transplantation, and the HCV population makeup was not significantly different between the liver and blood serum specimens of the individuals. Viral quasispecies complexity in serum was significantly lower after liver transplantation than before it, suggesting that certain HCV clones selectively proliferated after transplantation. Defective HCV clones lacking the structural region of the HCV genome did not increase in number, and full-genome HCV clones selectively increased in number immediately after liver transplantation. A re-increase in the same defective clone existing before transplantation was detected 22 months after transplantation in one patient. Ultradeep sequencing technology revealed that the genetic heterogeneity of HCV was reduced after liver transplantation. Dynamic changes in defective HCV clones after liver transplantation indicate that these clones have important roles in the HCV life cycle.